HOW CAN PATIENT PORTALS SUPPORT CAREGIVERS PROVIDING END-OF-LIFE CARE?: A MIXED-METHODS STUDY. (20th December 2022) - Portz, Jennifer Dickman; Powers, John David; Baldwin, Megan; Gleason, Kathy; Boxer, Rebecca; Palen, Ted; Bayliss, Elizabeth
Abstract: Patient portal design is rarely centered around patient caregivers—family members, friends and other designated persons who may access these digital tools for the patient's health needs. This study examines: (a) portal features used by caregivers during their loved-one's end-of-life; and (b) caregiver perceptions regarding the use of patient portals for caregiving near the end-of-life.Using sequential mixed-methods, we conducted a retrospective cohort analysis of caregiver proxy (N=137) use from 2016-2019 during their loved-ones' (N=5, 284) last 12 months of life and interviews with (N=31) 16-former and 15-current caregiver proxies. Caregiver proxy portal use in this population was lower than expected; however, caregivers who used the portal as proxies found value in tools for caregiving near the end-of-life. To leverage the patient portal to better support caregivers, future strategies should target caregiver portal adoption, awareness of beneficial portal tools, and the addition of caregiver specific resources and education.